PENGARUH EMOTIONAL FREEDOM TECHNIQUE (EFT) TERHADAP TINGKAT AGRESIFITAS PASIEN RESIKO PERILAKU KEKERASAN - Muliani, rizki; Abidin, Imam; Adawiyah, Ridha (Universitas 'Aisyiyah Bandung, 2019)
Mental disorders are abnormal conditions that are either physical or mental. Out of these neuropsychiatric conditions are recorded patients with different nursing issues, one of which is violent behavior. Aggression is a form of behavior that is intended to harm someone physically and mentally to violent behavior patients. Emotional Freedom Technique (EFT) is one of the therapies to address the problem of aggression in patients at risk for violent behavior, where EFT helps balance the energy in the body causing emotional disturbance. The purpose of this study was to find out the influence of EFT on the aggressiveness of patients' risk of violent behavior at West Java Provincial Hospital. The type of research used is pre-experiment with the design of One Group Pretest Posttest. The sample size was 19 with a purposive sampling technique. Data collection for aggression level using the Aggression Questionnaire, whereas for EFT implementation using EFT therapy implementation guide. EFT is performed for 5 days, 1 day for 7 minutes. Data were analyzed using the Paired T-test. The results showed that aggressiveness before EFT was nearly complete (89.5%) of high-risk patients with high levels of aggression, whereas aggressive levels after partial EFT (52.6%) of high-risk violence patients had high levels of aggression. The results showed p-value = 0.000 and it was concluded that there is an influence of the Emotional Freedom Technique on the level of aggression of patients at risk of violent behavior. Based on the results of this research it is recommended that the Emotional Freedom Technique (EFT) can be an alternative therapy in helping to deal with issues of aggression.